Cooligomerization of C9 fraction unsaturated hydrocarbons initiated by organic peroxides - Dzinyak, Bohdan (Publishing House of Lviv Polytechnic National University, 2014)
The work deals with the cooligimerization of C9 fraction unsaturated hydrocarbons of pyrolysis liquid products (PLP) obtained during ethylene production from diesel fuel. The main regularities of coologomerization initiated by peroxides have been determined, the influence of the main factors (temperature, process time, initiators nature and concentration) on the yield and physicochemical characteristics of the obtained cooligomers have been examined. The effective initiator of cooligomerization and optimal techno logical parameters of the process have been chosen. Робота присвячена дослідженню коолігомеризації ненасичених вуглеводнів фракції С9 рідких продуктів піролізу (РПП) дизельного палива виробництва етилену. Встановлено основні закономірності ініційованої пероксидами коолігомеризації ненасичених вуглеводнів фракції С9, з’ясовано характер впливу основних чинників (температури, тривалості реакції, природи та концентрації ініціаторів) на вихід і фізико–хімічні характеристики одержаних коолігомерів. Вибрано ефективний ініціатор коолігомеризації та оптимальні технологічні параметри процесу.
Ініційована органічними пероксидами коолігомеризація ненасичених вуглеводнів фракції С9
Keywords: pyrolysis liquid products; hydrocarbon; peroxide; petroleum resin; cooligomerization; pідкі продукти піролізу; вуглеводні; пероксиди; нафтополімерна смола; коолігомеризація